The Judge and the Precedent: Towards an Interpretation of the Separation of Powers - García López, Luisa Fernanda; Universidad del Rosario (Pontificia Universidad Javeriana, 2014)
The role of the judge during the Roman Republic was decisive and thenabolished and relegated to the “mouth of the law” with the French Revolution. For his part, the judge in the common scheme, he is creator of law and its role is determinant in the American legal system. The Colombian legal reality has been marked by a leading role of constitutional jurisprudence in the area of fundamental rights and public policies. To that extent, the separation of powers in Colombia is due to a figure that has developed since 1991. The classical conception of the separation of powers or balance of powers has been reinterpreting; a new version involves the judge and the precedent. Jurisprudence as a source of law in the time of the Roman Republic, its absolute rejection in the French Revolution and its reinterpretation in the 20th century, are evidence of the inclusion of the judge on the constitutional stage as the guarantor of democracy and of a living right. Undeniably the political role as a creator of law by the constitutional judge, define and interpret the content of the Constitution. Therefore, the current democracy responds to a reinterpretation of the separation of powers and the inclusion of the judge on the legal stage. To that extent, the scope of the judicial activism responds to an interpretive activity and creation of judges under the name of precedent. In Colombia, this activism through the Acción de tutela, has generated great achievements at the level of recognition of fundamental rights and primacy of agile and effective legal mechanisms, but more than anything else, it reflects the shortcomings of a legal system that does not respond to the needs of the society. What are the limits of a Constitutional Court that has revolutionized the Colombian legal universe? Certainly article 241 of the COP, which implies not exercise functions of other powers, not “become legislator, replace the Government in the policy direction or decide the causes of ordinary jurisdiction”. However, as its main functions are, exercise control over constitutionality of laws and the defense of fundamental rights, it is difficult to set limits to the constitutional courts. It is necessary to the image of the common law to create the jurisprudential corpus and a series of precise parameters that generate harmony, from the resolution of cases fill the gaps and above all to create legal certainty.